A Comparison of Obstacle Dependent Gaussian and Hybrid Potential Field Methods for Collision Avoidance in Multi-Agent Systems. Issue 1 (26th April 2021) - Candan, Fethi; Peng, Yusheng; Mihaylova, Lyudmila
No abstract available